Comprehensive Approach to Enhancing Security Evaluation Parameters for Image Encryption (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper presents a comprehensive approach to enhancing security evaluation parameters for image encryption. Image encryption plays a crucial role in safeguarding visual data from unauthorized access and malicious attacks. Existing evaluation parameters often focus on traditional cryptographic metrics such as encryption speed and resistance against known attacks. However, with the advent of advanced computing technologies and sophisticated cyber threats, there is a growing need to reassess and augment these parameters. Our approach begins by reviewing current encryption techniques and identifying their strengths and vulnerabilities. We then propose enhancements that integrate advanced cryptographic algorithms, robust key management strategies, and efficient image compression techniques. These enhancements aim to strengthen confidentiality, integrity, and availability of encrypted images while mitigating risks posed by quantum computing and adaptive adversaries. the paper discusses the importance of evaluating encryption schemes across various image types and scenarios to ensure comprehensive security coverage. Future research directions include implementing these enhancements in practical settings and evaluating their effectiveness against emerging threats. This comprehensive approach seeks to advance the field of image encryption by providing a structured framework for enhancing security evaluation parameters, thereby enhancing the protection of visual data in today’s increasingly digital and interconnected world.